Arts Practice: Chaos, Order, and Disequilibrium - Green, Miik (Common Ground, 2014)
This paper explores notions of chance and chaos in arts practice, aligning the author’s artistic practice with the Deleuzian concept of rendering ‘unseen forces visible’. The visual artist, through studio process, can reveal unseen forces similar to those that exist in the biological world. This research references the fields of art and science, comparing the art studio to that of the science laboratory, where an artist approaches materials as an industrial chemist might, combining matter in disequilibrium. Forms representative of diatoms, pollen and radiolaria manifest in this process, appearing as encapsulated experiments. By capturing, suspending, or pausing these material interactions, one can visualise these structures. The paintings referenced here seek to unconceal through an active disequilibrium, where pigments separate, resin seals and tension reveals. The light that is refracted and reflected through and by this metamorphosis changes the nature of the materials: inks and resin turn from liquid to solid, darkness to light.